Ruolo neuroprotettivo del sistema istaminergico e delle HSPs nella risposta allo stress ambientale nell’encefalo del Teleosteo Thalassoma pavo - Giusi, Giuseppina; Tota, Bruno; Facciolo,Rosa Maria (My University, 2014)
At date, a plethora of evidence regarding adverse morpho-functional and neurobiological aspects provoked by environmental stressors has been considered. Following exposure to stress factors, the activation of both specific neurosignaling mechanisms and molecular pathways account for the modulation of complex adaptative processes in animal targets. In this context, the aim of the present work is to analyze the neuroprotective role of histaminergic system and heat shock proteins towards environmental neurotoxicants such as heavy metals and pesticides in the Teleost Thalassoma pavo. Such environmental stressors account for significative alterations on motor and feeding behaviors, which are tightly correlated to neurodegenerative processes in key brain regions. In this work, the molecular characterization of H2R and H3R permits to demonstrate a conservation of specific sequences, which appear to be determinant for the function of such subtypes in phylogenetically distant Vertebrates. Moreover, the inactivation of H2R and H3R, via the application of selective antagonists (Cimetidine and Thioperamide, respectively), induces in Thalassoma pavo abnormal behaviors and trascriptional alterations, suggesting a clear physiological role of this neuronal system in our model. The expression pattern of histaminergic system results to be highly modified following exposure to environmental stressors in a region-dependent manner. In particular, the heavy metals induce downregulations of H2R mRNA in some brain regions such as mesencephalon, which is involved in the regulation of motor activities. On the other hand, both heavy metal and pesticides account for an increasement of H3R trascriptional levels in hypothalamic and telencephalic areas. From the concomitant exposure to histaminergic antagonists and environmental stressors, it was possible to demonstrate that H2R blockade is responsible for enhanced stressors-dependent neurotoxic effects. On the contrary, the inhibition of H3R activities accounts for an amelioration of both abnormal motor behaviors and neuronal damage induced by such environmental stressors. Consistent with the effects on histaminergic system, heavy metals and pesticides also promote the activation of cellular defence processes through the stimulation of heat shock proteins trascription, i.e. HSP90 e HSP70. The histaminergic antagonists are able to influence heat shock proteins expression, inducing a heterogeneous pattern of HSP90 trascription levels, while in the case of HSP70 an enhanced expression is typical of all encephalic areas. The results of the present work demonstrate, for the first time in an aquatic Vertebrate, a possible interactions between histaminergic system-dependent neurosignaling activities and HSPs network, which could be represent an important neurophysiological mechanism operating during neuronal stress conditions.
Dottorato di Ricerca in Biologia Animale, XIX Ciclo
Keywords: Fisiologia animale